2021
DOI: 10.7759/cureus.20159
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasonography in Intraperitoneal Bladder Rupture With Delayed Presentation

Abstract: Delayed presentation of intraperitoneal rupture of the urinary bladder in a child after blunt trauma is a rare occurrence. On ultrasonography, diagnosis of bladder injuries has been sparsely reported in the literature. We report a case of intraperitoneal bladder rupture in a four-year-old child and describe the role of ultrasonography in providing a prompt and accurate diagnosis of the entity as mortality increases if surgical repair is delayed. On high-resolution ultrasonography, rent was noted in the urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Interestingly, these values did not differ greatly between hypotensive and normotensive patients. Abdominal free fluid was also reported in all traumatic and atraumatic case reports of intraperitoneal bladder rupture evaluated with radiologist- or technician-performed ultrasound 14 , 21 , 22 , 23 , 25 , 26 , 27 . Similarly, our case showed large volume of free fluid in Morison’s pouch and the rectovesical pouch with the patient reclined in Trendelenburg position, which increases sensitivity for free fluid 28 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, these values did not differ greatly between hypotensive and normotensive patients. Abdominal free fluid was also reported in all traumatic and atraumatic case reports of intraperitoneal bladder rupture evaluated with radiologist- or technician-performed ultrasound 14 , 21 , 22 , 23 , 25 , 26 , 27 . Similarly, our case showed large volume of free fluid in Morison’s pouch and the rectovesical pouch with the patient reclined in Trendelenburg position, which increases sensitivity for free fluid 28 .…”
Section: Discussionmentioning
confidence: 91%
“…Most prior cases of bladder rupture diagnosed by ultrasound occurred in the setting of trauma using the Focused Assessment with Sonography for Trauma (FAST) examination 21 , 22 , 23 . A 2019 systematic review and meta-analysis reported that POCUS was 74% sensitive and 98% specific for intra-abdominal free fluid in trauma 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation